Tat Twam Asi Local Wisdom Based Learning Video Religious Diversity Material for Grade V Elementary School - Aristya Julianingsih, Ni Komang; Gede Agung, Anak Agung; Arie Paramitha, Made Vina (Universitas Pendidikan Ganesha, 2024)
Student learning outcomes are still low, especially in the subject of religious diversity. This is due to teachers' limited understanding of developing teaching media that meets students' needs. This study aims to produce media in the form of instructional videos to support the learning process for fifth-grade elementary school students. This type of research is developmental research using the ADDIE model. The subjects in this study are (1) design experts, (2) subject matter experts, (3) instructional design experts, (4) media experts, (5) individual trials and small group trials, and (6) field trials/student effectiveness. Data collection methods used include tests and questionnaires. The data analysis techniques used are quantitative descriptive analysis and inferential statistical analysis. The results of the study are: (1) The design of the instructional video media received an evaluation score of 97.56% from the design experts, with a qualification of very good; (2) The video media is deemed feasible based on the evaluations from the subject matter experts (91.67%, very good), instructional design experts (92.5%, very good), media experts (93.33%, very good), individual trials (95.83%, very good), and small group trials (93.89%, very good). Based on the t-test results, the calculated tvalue is greater than the ttable value (6.886 > 1.706), so H0 is rejected and H1 is accepted. It can be concluded that the instructional video based on local wisdom, Tat Twam Asi, is effective in teaching the religious diversity topic in Pancasila education for fifth-grade elementary school students. The implementation of the instructional video requires facilities, teacher commitment, and support from the school principal.